A case study of death due to burn - Hossain, Md Nazir; Uddin, Shafique Md Jashim; Uddin, Md Jasim; Ray, Debika; Hoque, Mazharul (Journal of Dhaka National Medical College & Hospital, 2023)
Injuries due to burns are known to have a very high mortality rate. Burn injuries occur due to a variety of thermal, electrical, mechanical products and can be accidental, suicidal or even homicidal in nature. As the inquiry and research are limited to identifying patterns and causes for burns, the accurate originator and mechanisms are not clearly known. Herein we are going to discuss a case report of 18 years unmarried female was the victim of accidental burn in domestic affair when she was preparing breakfast in the kitchen for her family. J. Dhaka National Med. Coll. Hos. 2023; 29 (01): 45-48